A rare case of Salmonella Typhi Meningitis in an eleven month old infant: a case report (2012)
Non-typhoidal Salmonella are infrequent causes of childhood meningitis. Most reports of Salmonella typhi meningeal infections are confined to neonates. A rare instance of S. typhi in an otherwise healthy eleven month old infant is being reported.